Developing Consciousness-Raising Based Grammar Material for English Beginner Level at English Course - Nurul Arifin (Language-Edu, 2019)
AbstractSince the beginning of language studies, Second Language Acquisition (SLA) researchers have been searching for effective ways of developing learners’ grammar learning materials. This study aimed at developing grammar material at an English course in Pare, Kediri. Consciousness-raising (CR) takes a part as the approach used by the researcher in developing the grammar material which has five steps on the process of material delivery. The first is building the students’ background knowledge by showing some examples of the grammar rules in use related to the topic on the book which then, lead the students to comprehend implicitly the use of the rules, after that, students were asked to practice the grammar rule in use by giving them exercises, then researcher made sure the students had known the use of the grammar rule by giving them some error analysis task then the last, students’ enrich their knowledge of rule by stepping to the new grammar rule which has been provided on the book and those activity were done in sequence for each topic of the grammar rule on the book. The product of the research is a book which is used in teaching grammar for beginner level. The product revised based on the two experts’ judgment on the developed product. The revised product was revised and then tried it out on 16 students as the participants at the course. Then 10 questioners were done by students to know their opinion towards the developed product. The percentage of the questioners got 87.5%. It indicates that the revised book is very good to be used as the learning material of grammar skill. Furthermore, it will help students in comprehending the learning of grammar rules easily and it will also be beneficial for English course teachers who are finding out ways of improving students’ comprehension on grammatical skill. Keywords: Developing, Grammar material, Beginner level, Consciousness-raising.